Medical Care and Crimes in German Occupied Poland, 1939–1945: New Findings, Interpretations and Memories - Ley, Astrid; Cuerda-Galindo, Esther; Ciesielska, Maria (Metropol Verlag, 2022)
The volume contains the papers of several (medical) historians and medics from Europe and Israel on Nazi medical crimes in Poland. They are based on presentations at the conference “Building Memory – Building Resilience” 2018 in Warsaw and Lublin which focused on the question of how prospective physicians and other healthcare employees can gain professionally relevant knowledge from Nazi era medical transgressions even today, more than 75 years after the end of the war.Also included were an introductory overview by Robert Traba on the culture of remembrance in Poland concerningWorld War II and the Holocaust and a personal account by Zofia Karłowicz-Perzynska about her grandfather Juliusz Zweibaum.